An empirical analysis of evaluating new urbanization's sustainable development—Taking Anhui as an example. Issue 4 (19th May 2017) - Aijun, Li; Chengwen, Wang
Abstract: The new urbanization construction is an important initiative to promote and speed up the healthy and sustainable development of Chinese economy. It is also an important means of realizing the moderately prosperous society, socialist modernization and the rejuvenation of the Chinese nation. Moreover, it is also an important means of solving issues related to "agriculture, farmer and rural area". Therefore, objectively evaluating the sustainable development of each region's urbanization, determining their developmental situations and finding out their advantages and disadvantages bring convenience for each region to formulate relevant policy guidance and point out the direction for new urbanization construction. Combining the AHP and DEA methods, this paper uses the qualitative and quantitative methods to set up the system of evaluating new urbanization's sustainable development from the situations of economic development, the social development and the resource environment. It sets up the evaluation model, thereby forming a feasible evaluation method. This paper also carries out an empirical analysis of the data related to 16 prefecture-level cities in Anhui Province and proves this evaluation method is reasonable and valid, thereby providing a scientific basis for formulating relevant polices to promote the new urbanization's sustainable development.